Materials 4.0: Materials big data enabled materials discovery - Rajan, Jose; Seeram, Ramakrishna (Elsevier Ltd, 2018)
Materials discovery is an incessant process and has been the landmark of human progress. This article sees the evolution of materials discovery in generations, its current generation as the fourth paradigm of materials research and term it as Materials 4.0, briefly describe the built-up infrastructure for the Materials 4.0, and cite few examples of materials discovery and lifecycle assessment under this protocol.